(untitled) (American Journal of Islam and Society, 1993)
During the last two decades, the politics of certain Arab countries have been influenced by various Islamic groups. Some of these groups have expressed their dissatisfaction with the performances of their governments by Using the available political channels to seek change; others have resorted to violence. Armed protests have taken the form of bombings, assassinations, and mass demonstrations. Suicide attacks and armed struggle took place against Israeli, American, and French forces in Lebanon (1982-83). President Sadat of Egypt was assassinated in 1981 by Egyptian military pemnnel who were members of an Islamic movement. Another armed struggle against the Syrian regime was initiated by the Syrian Islamic Front in 1976-82. Numerous demonsttations against the governments of Morocco, Algeria, and Tunisia took place during the 1980s. Other Muslim groups attempted to participate in the decision-making process in their countries. The Society of Muslim Brothers in Egypt encouraged its prominent members to run for election to the Egyptian Parliament. However, the Society was not considered a legal party according to Egyptian law. The Wafd, a legitimate party, allowed the Society of Muslim Brothers to campaign under their banner. As a result, members of the Society voted in accordance with their ideological and political beliefs rather than the Wafd party line. In Jordan, the Society of Muslim Brothem campaigned as an independent party during the 1988 elections and won twenty percent of the seats. Due to the Arab countries’ economic and strategic importance, various govemments, scholars, and private and public organizations have paid close attention to these incidents. In an attempt to understand this phenomenon, academic conventions have been held, books and articles have been published, and gmnts have been awarded for research. Western and Arab scholars have described it with such labels as Islamic fundamentalism, revivalism, awakening, reformism, resurgence , renewal, militancy, or simply ...